Sjögren’s Syndrome Complicated by Myeloid/Natural Killer Cell Precursor Acute Leukemia: Case Report and Review of the Literature - Hao Feng; Jianlin Qiao; Ningning Ding; Wei Chen; Kunming Qi; Xiuying Pan; Jiang Cao; Kailin Xu (Case Reports in Hematology)
We report a case of Sjögren’s syndrome (SS) complicated by myeloid/natural killer (NK) cell precursor acute leukemia (M/NKPAL). A 75-year-old woman with a previous SS history for 2 years was routinely treated. Peripheral blood progenitor cells were increased, and subsequent bone marrow cell morphology examination showed the presence of acute myeloid leukemia type M4. However, flow cytometry analysis revealed that CD7/CD56/CD33/CD34/HLA-DR/cCD3 were all positive and myeloperoxidase- (MPO-) specific staining, other T cells, NK cells, and myeloid markers were all negative. Clonal T-cell receptor (TCR)β/TCRγ/TCRδ gene rearrangements and Epstein-Barr virus (EBV) were negative. The diagnosis of M/NKPAL was therefore confirmed. Unfortunately, this patient did not receive chemotherapy and later died of acute left heart failure and respiratory failure. SS complication with M/NKPAL is relatively rare. Combined with the relevant literatures, our study offers new insights into the clinical characteristics, pathological features, possible pathogenesis, and differential diagnosis of this rare disease.